The influence of physicians' specialty on prescribing patterns at a general medicine out-patients clinic - Ofori-Adjei, Yaw A (Ghana Med J, 2019)
BACKGROUND: Several factors have been identified that influence physicians' prescribing habits. The influence of physician's specialty has not been studied. This study is to determine if there are differences in the prescribing patterns amongst these various specialities that run a general medicine clinic at a tertiary hospital in Ghana. METHODS: Data collected from the out-patients clinic attendance records were analysed using WHO Rational Use of Medicines indicators. Analysis of Variance Test was carried out to establish if there was any variance in the prescribing indicators amongst 4 units of Physicians. RESULTS: 678 patient encounters were utilised for this study. The average number of drugs prescribed per encounter was 4.4, drugs prescribed by generic name was 86.9%, patient encounters in which antibiotics prescribed were 6.5% (n= 44) and injections were prescribed in 3.2% (n=22) of patient encounters. 64.0% of all drugs prescribed were from the Ghanaian EML. The unit of the physician did not have a significant effect on the average number of medicines prescribed per patient encounter (F (3, 674) = 2.19, p = 0.088), and the percentage of medicines that were prescribed from the Essential Medicines List (F (3, 674) = 1.52, p = 0.207). The unit the physician belonged to however did have a significant effect at p < 0.05 on the prescription of generic medications (F (3, 674) = 4.79, p = 0.003). CONCLUSION: The physician units did not differ in their prescribing patterns at the general medicine clinic except for prescription of drugs by their generic names. FUNDING: None declared